Development and Validation of Stability Indicating RP-HPLC Assay Method for Mefenamic Acid - Fernandes, Adison; Sanjay Pai, P.N. (Asian Journal of Chemistry, 2019)
The present research work was carried out to evaluate the stability behaviour of mefenamic acid under ICH Q1A (R2) recommended stress conditions. The drug was subjected to hydrolytic, oxidative, photolytic and thermal stress conditions. The drug was found susceptible to degradation under oxidative stress condition but was stable under hydrolytic, photolytic and thermal stress conditions. A total two degradation products were formed, which were separated using HPLC. The chromatographic separation was carried out on Sunfire ODS C-18 (250 × 4.6 mm, 5 μm) column. Optimum resolution was obtained using ammonium dihydrogen phosphate buffer (10 mM, pH 4) and acetonitrile programmed in isocratic elution mode in the ratio of 45:55 v/v at 225 nm using photodiode array detector at a flow rate of 1 mL/min. The designed method was validated as per ICH Q2 (R1) guidelines. The response of drug was linear in the concentration range of 10-100 μg/mL (R2 = 0.9998). The method was found specific, precise and accurate. The mean accuracy was found to be 100.46 %. The developed method was successfully applied for the analysis of marketed formulation.